Exploring Students' Attitudes and Interests in Learning Chemistry: A Survey of Junior High Schools in Bengkalis during Kurikulum Merdeka Implementation - Astuti, Wiji; Ikhsan, Jaslin (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
Technological advances require education to continuously adapt, including through the implementation of the Kurikulum Merdeka, which emphasizes student-centered learning. This study aimed to describe the attitudes and interests in learning chemistry among junior high school students in Bengkalis Regency and to analyze gender-based differences during the Kurikulum Merdeka era. This quantitative research used a descriptive survey approach with a stratified random sampling technique involving seventh- and eighth-grade students from nine public junior high schools. A Likert-scale questionnaire measured four attitude indicators (perceived importance of chemistry, learning comfort, perceived difficulty, and usefulness of chemistry) and four interest indicators (attention, interest, enjoyment, and active involvement). The results showed that students’ attitudes toward learning chemistry were positive (73.99%), with the highest mean score (4.19) on the usefulness of chemistry indicator. Interest in learning chemistry was also positive (M = 3.92; 74.98%). A t-test indicated no significant gender differences in attitudes (p = 0.115 > 0.05) or interest (p = 0.677 > 0.05). These findings highlight the positive role of the Kurikulum Merdeka in fostering equitable learning experiences and support Sustainable Development Goal (SDG) 4: Quality Education by promoting inclusive, student-centered learning that enhances scientific literacy and lifelong learning skills.